Association of metabolic syndrome with hypothyroidism and hyperuricemia: A cross-sectional study in a tertiary care hospital, Kolkata, West Bengal - Atanu Chakraborty; Amitabha Pal; Sudipta Pal; Saswati Mukherjee (Asian Journal of Medical Sciences, 2023)
Background: Metabolic Syndrome (MetS) (Syndrome X, insulin resistance syndrome, MetS) consists of a constellation of metabolic abnormalities which include central obesity, hyperglycemia, insulin resistance, high triglycerides, low high-density lipoprotein (HDL) cholesterol, and hypertension. Obesity is a critical component of MetS. It causes alteration in the thyroid hormones and hyperuricemia. Furthermore, insulin resistance seen in MetS causes decreased uric acid excretion. Aims and Objectives: To study the association of MetS with hypothyroidism and hyperuricemia. Materials and Methods: A cross-sectional study was conducted among patients from the outpatient department of General Medicine, IPGME and R, Kolkata from January 2012 to June 2013. A total of 112 patients, consisting of 53 patients with MetS and 59 patients without MetS were selected. Patients’ history, clinical and laboratory findings were recorded and data were analyzed. Results: Majority (66%) of the patients with MetS were female and the rest were male. The mean Body mass index of patients with MetS was 33.31±4.36 (Mean±SD) kg/m2 and without MetS was 25.21±2.62 (Mean±SD) kg/m2. A significant association was observed between weight, height, waist circumference, fasting blood sugar, HDL value, and MetS (P<0.05). About 39.6% of the patients with MetS had hyperuricemia. The association between MetS and hyperuricemia was found to be significant. Similarly, 45.3% of the patients with MetS had hypothyroidism. This association was also found to be significant. Serum thyroid-stimulating hormone had a minimal correlation with serum uric acid in patients with MetS (correlation coefficient r=0.344), while no correlation was observed between fT3, fT4 with serum uric acid. Conclusion: Increased prevalence of hyperuricemia and hypothyroidism was seen among patients with MetS. More extensive population-based research is needed to support this finding.